Differentiation of Mesenchymal Stem Cell toward the Insulin-like Cells with Lentivirus Vector Mir-375 - Hossein Sazegar; Negar Azarpira; Akbar Vahdati; Mohamad hossein Karimi; Masoud Soleimani (Fasa University of Medical Sciences, 2016)
Background & Objective: Type1 diabetes is characterized by autoimmune destruction of pancreatic β cells, leading to reduced insulin secretion. Differentiation of mesenchymal stem cells (MSCs) into β-like cells offers new ways of diabetes treatment. MSCs can be insulated from the human umbilical cord tissue and differentiate into insulin-producing cells. Material & Methods: Human umbilical cord-derived stem cells (hUDSCs) were attained after birth, selected by plastic adhesion, and considered by flow cytometric analysis. For the differentiation induction, miR-375 was lentivirally over expressed in hUDSCs. Results: Meaningful that microRNAs (miRNAs) are the key players in several stages of pancreatic Differentiation, we have presented a novel and cost-effective strategy in which the over-expression of miR-375 promotes the pancreatic differentiation in hUDSCs in the absence of any other stimulator. The major expressions of PDX1 and insulin were identified by quantitative Reverse Transcription Polymerase Chain Reaction (RT-PCR) (P <0.05). Conclusion: In conclusion, the Morphological assessment and the expression analysis of islet marker genes demonstrated that hUDSCs are able to differentiate into insulin-producing cells by transduction with lentiviral vector miR-375